Unpacking Figurative Language and Idiom in Eminem’s Mockingbird - Setiawan, Adenin Faradillah; Afrianto, Afrianto (Universitas Muhammadiyah Barru, 2026)
This study aims to identify and analyze the types of figurative language and idiomatic expressions in Eminem's song “Mockingbird,” and to explain the meanings that lend emotional depth to the lyrics. This study uses a qualitative descriptive method because it focuses on the interpretation of literary elements in song lyrics. The research data consists of words, phrases, and lines of lyrics that contain figurative language and idioms. The data were interpreted using Perrine’s framework of figurative language and McCarthy and O’Dell’s classifications of idiomatic expressions. The results show that the lyrics contain several types of figurative language, such as metaphors, symbols, hyperbole, and irony, as well as idioms that reinforce the emotional nuances and natural language style. These expressions represent the themes of fatherly love, trauma, protection, regret, and determination. Overall, this study concludes that the figurative language and idioms in the song “Mockingbird” not only serve as stylistic embellishments but also as important devices that deepen the meaning and enhance the aesthetic appeal and emotional value of the song's lyrics.